Genetic mapping of the Andean anthracnose resistance gene present in the common bean cultivar BRSMG Realce - Lucas Matias Gomes-Messias; Rosana Pereira Vianello; Gabriella Ribeiro Marinho; Luana Alves Rodrigues; Alexandre Siqueira Guedes Coelho; Helton Santos Pereira; Leonardo Cunha Melo; Thiago Lívio Pessoa Oliveira de Souza (Frontiers in Plant Science, 2022)
The rajado seeded Andean bean (Phaseolus vulgaris L.) cultivar BRSMG Realce (striped seed coat) developed by Embrapa expressed a high level of anthracnose resistance, caused by Colletotrichum lindemuthianum, in field and greenhouse screenings. The main goal of this study was to evaluate the inheritance of anthracnose resistance in BRSMG Realce, map the resistance locus or major gene cluster previously named as Co-Realce, identify resistance-related positional genes, and analyze potential markers linked to the resistance allele. F2 plants derived from the cross BRSMG Realce × BRS FC104 (Mesoamerican) and from the cross BRSMG Realce × BRS Notável (Mesoamerican) were inoculated with the C. lindemuthianum races 475 and 81, respectively. The BRSMG Realce × BRS FC104 F2 population was also genotyped using the DArTseq technology. Crosses between BRSMG Realce and BAT 93 (Mesoamerican) were also conducted and resulting F2 plants were inoculated with the C. lindemuthianum races 65 and 1609, individually. The results shown that anthracnose resistance in BRSMG Realce is controlled by a single locus with complete dominance. A genetic map including 1,118 SNP markers was built and shown 78% of the markers mapped at a distances less than 5.0 cM, with a total genetic length of 4,473.4 cM. A major locus (Co-Realce) explaining 54.6% of the phenotypic variation of symptoms caused by the race 475 was identified in Pv04, flanked by the markers snp1327 and snp12782 and 4.48 cM apart each other. These SNPs are useful for marker-assisted selection, due to an estimated selection efficiency of 99.2%. The identified resistance allele segregates independently of the resistance allele Co-33 (Pv04) present in BAT 93. The mapped genomic region with 704,867 bp comprising 63 putative genes, 44 of which were related to the pathogen-host interaction. Based on all these results and evidence, anthracnose resistance in BRSMG Realce should be considered as monogenic, useful for breeding purpose. It is proposed that locus Co-Realce is unique and be provisionally designated as CoPv04R until be officially nominated in accordance with the rules established by the Bean Improvement Cooperative Genetics Committee.